2014
DOI: 10.2105/ajph.2013.301431
|View full text |Cite
|
Sign up to set email alerts
|

Work in Multiple Jobs and the Risk of Injury in the US Working Population

Abstract: Our findings suggest that working in multiple jobs is associated with an increased risk of an injury, both at work and not at work, and should be considered in injury surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 13 publications
1
37
2
1
Order By: Relevance
“…Because of the large variation in exposure and outcome definitions as well as measurement methods, a meta-analysis was not feasible. However, when grouping similar exposures together, the risk for occupational injuries was consistently higher for those performing multiple jobs compared with one (15,16,20,21) and among those employed through a subcontractor at the same worksite or staffing agency (14,22,23). The latter has also been found in a research report by the Swedish Work Environment Agency, which did not the meet the peer-reviewed criteria for inclusion (30).…”
Section: Highmentioning
confidence: 85%
See 2 more Smart Citations
“…Because of the large variation in exposure and outcome definitions as well as measurement methods, a meta-analysis was not feasible. However, when grouping similar exposures together, the risk for occupational injuries was consistently higher for those performing multiple jobs compared with one (15,16,20,21) and among those employed through a subcontractor at the same worksite or staffing agency (14,22,23). The latter has also been found in a research report by the Swedish Work Environment Agency, which did not the meet the peer-reviewed criteria for inclusion (30).…”
Section: Highmentioning
confidence: 85%
“…A majority of the studies reported a positive association between precarious employment and occupational injuries. All of the four studies on multiple job holders indicated that the risk for occupational injuries was higher among these individuals compared to those with only one job (15,16,20,21). Being employed through a subcontractor at the same worksite or staffing agency was also associated with a higher risk of occupational injuries compared to being directly employed by the employer (14,22,23).…”
Section: Dimensions Of Precarious Employment Studied and Their Associmentioning
confidence: 98%
See 1 more Smart Citation
“…Working in multiple jobs has been found to be associated with an increased risk of work and non-work injury, which includes higher absenteeism rates. This is presumably due to increased fatigue, lack of sleep, or additional physical and mental stress from being exposed to disruptive or irregular work environments and timetables [13]. Additional psychosocial stress has also been seen as a result of the combined impact and interaction of multiple jobs.…”
Section: The Hazards Of Multiple Job-holdingmentioning
confidence: 99%
“…The few studies on the consequences of MJH have generally focused on health effects and have all been conducted in the US. These studies suggest that MJH is associated with an increased risk of injuries and less sleep 5, 6…”
Section: Introductionmentioning
confidence: 90%